OBTENÇÃO E CARACTERIZAÇÃO FÍSICO-QUÍMICA DE QUEIJO TIPO REBLOCHON ELABORADO COM LEITE BOVINO DAS RAÇAS HOLANDESA E JERSEY - Jaster, Henrique (2014)
The Reblochon, one of the most important cheeses in France, presents peculiar aroma and flavor characteristics due to the ripining process by the yeast Geotrichum candidum, and has attracted interest in Brazilian cheese sector. However, there is just a little information about technology and quality characteristics of Reblochon processing. Adjusting the product to consumers in Brazil covers several steps, from the composition of the milk used, until the protocol definition of fabrication and quality standards that must be defined during the ripining process. Thus, the present study aimed to evaluate and define some quality parameters of type Reblochon cheese during the ripining process. Bovine milk Holstein and Jersey were used as raw materials for the production of Reblochon cheese. The results show that the humidity content remained on average 50% during the whole process of ripining (21 days). The total ash or mineral showed the highest concentrations at the cheese surface after 14 days ripining. The fat was on average 5% higher for the cheeses made with milk from Jersey cows than from Holstein. The color parameters showed a reduced brightness (L) along the ripining and decreased the a* values at the surface and increased in the center of the cheese. The proteolysis was high on in the cheeses made with milk from Holstein, and also on the surface of both cheeses. Texture analysis showed that the hardness, gumminess and chewiness showed an increase in the first 7 days of ripining and decreased from the 14th day of ripining. The cohesiveness and elasticity decreasedin cheeses after 21 days of ripining. A strong correlation between ripining time and NPN (r = 0.87), cohesiveness (r = -0.86) and resilience (r = -0.92) was observed. Elasticity x NPN (r = -0.96; regarding the physical characteristics correlated with the physicochemical, were found significant values for Hardness x protein (r = 0.85), tirosina x elasticity (r = -0.89), tirosina x cohesiveness (r = -0.86), cohesiveness x NPN (r = -0.88), and Resilience x NPN (r = -0.89). Therefore, the results indicate the quality parameters for the Reblochon type cheese. Changes after 14 days of ripining modify some analyzed attributes and the product begins to have identity of Reblochon cheese indicating the beginning consumption.